Comparative Genomics Reveals Evidence of Genome Reduction and High Extracellular Protein Degradation Potential in Kangiella - Wang, Jiahua; Lu, Ye; Nawaz, Muhammad Z.; Xu, Jun (Frontiers in Microbiology, 2018)
Abstract The genus Kangiella has recently been proposed within the family Kangiellaceae, belonging to order Oceanospirillales. Here, we report the complete genome sequence of a novel strain, Kangiella profundi FT102, which is the only Kangiella species isolated from a deep sea sediment sample. Furthermore, gaps in the publicly available genome scaffold of K. aquimarina DSM 16071 (NCBI Reference Sequence: NZ_ARFE00000000.1) were also filled using polymerase chain reaction (PCR) and Sanger sequencing. A comparative genomic analysis of five Kangiella and 18 non-Kangiella strains revealed insights into their metabolic potential. It was shown that low genomic redundancy and Kangiella-lineage-specific gene loss are the key reasons behind the genome reduction in Kangiella compared to that in any other free-living Oceanospirillales strain. The occurrence of relatively diverse and more frequent extracellular protease-coding genes along with the incomplete carbohydrate metabolic pathways in the genome suggests that Kangiella has high extracellular protein degradation potential. Growth of Kangiella strains has been observed using amino acids as the only carbon and nitrogen source and tends to increase with additional tryptone. Here, we propose that extracellular protein degradation and amino acid utilization are significant and prominent features of Kangiella. Our study provides more insight into the genomic traits and proteolytic metabolic capabilities of Kangiella. Keywords: Marine bacteria, Oceanospirillales, Kangiella, genome reduction, protein degradation